Does the introduction of newborn hearing screening improve vocabulary development in hearing-impaired children? A population-based study in Japan. Issue 2 (February 2015) - Ohmori, Shuhei; Sugaya, Akiko; Toida, Naomi; Suzuki, Etsuji; Izutsu, Masato; Tsutsui, Tomoko; Kataoka, Yuko; Maeda, Yukihide; Fukushima, Kunihiro; Nishizaki, Kazunori
Abstract Objective Permanent hearing impairment has a life-long impact on children and its early identification is important for language development. A newborn hearing screening (NHS) program has started in Okayama Prefecture, Japan, in 1999 to detect hearing impairment immediately after birth. We aim to examine the effect of this screening program on vocabulary development in pre-school children in a before and after comparative study design. Methods A total of 107 5-year-old children who graduated from Okayama Kanariya Gakuen (an auditory center for hearing-impaired children) between 1998 and 2011 were enrolled in this study. The pre-NHS group (n = 40) was defined as those who graduated between 1998 and 2003, while the post-NHS group (n = 67) was defined as those who graduated between 2004 and 2011. The primary outcome was receptive vocabulary, which was assessed by the Picture Vocabulary Test [score <18 (low) vs. score ≥18 (high)]. The secondary outcome was productive vocabulary, or the number of productive words, which was assessed by an original checklist [<1773 words (low) vs. ≥1773 (high)]. We calculated odds ratios and 95% confidence intervals for vocabulary development and compared both groups. Results The adjusted Picture Vocabulary Test score and number of productive words were significantly higher (p < 0.01) in the post-NHS group than the pre-NHS group. Odds ratios were 2.63 (95% confidence interval: 1.17–5.89) for receptive vocabulary and 4.17 (95% confidence interval: 1.69–10.29) for productive vocabulary. Conclusions The introduction of NHS in Okayama Prefecture significantly improved both receptive and productive vocabulary development in hearing-impaired children.